Madame Bovary - Flaubert, Gustave 1821-1880; Rózsa, Miklós 1907-1995 (Turner Entertainment [u.a.], 2007)
A woman, not satisfied with the limited life she leads, rebels against conventional society, and finds tragedy.
Bildformat 1.37:1
Orig.: USA 1949
Enth. theatrical trailer
Keywords: Flaubert, Gustave <1821-1880> - Adaptations cinématographiques et télévisées; Geschichte 1800-1900; Adultery - Drama; Bovary, Emma (Fictitious character) - Drama; Drames (Cinéma); Films d'amour; Longs métrages - États-Unis; Wives - Social conditions - France - Drama; Women - Social conditions - France - Drama; Frau; Adultery -- France -- Drama; Bovary, Emma (Fictitious character) -- Drama; Wives -- France -- Social conditions -- Drama; Women -- France -- Social conditions -- Drama; France - Social conditions - 19th century - Drama; Frankreich; France -- Social conditions -- 19th century -- Drama; Feature films; Video recordings for the hearing impaired